The Christian Character of Certain Liberal Arts Colleges with a Focus on the Academic Arena - Dundon, Mary Catherine (Sociological analysis, 1971)
The purpose of this study was to determine whether Catholic colleges have a distinctive Christian character with respect to their academic beliefs and practices as perceived by their academic deans. The Christian Character Questionnaire (CCQ) was designed by the writer from post-Vatican Council II descriptions of the contemporary Catholic college or university. The CCQ consists of 45 statements to be answered in two ways, evaluating both the real and the ideal academic beliefs and practices of the faculty and administration of the college. The subjects consisted of academic deans from a random sample of 42 Catholic, 42 Protestant, and 41 non-sectarian colleges. Ninety-nine responded.Statistical analyses indicated strong agreement between responses of Catholic and Protestant college deans. Since the particular interest of this study was the relationship between responses of the Catholic and non-sectarian college deans, the 42 (out of 90) items in which they differed significantly were proposed as indicators of a distinctive Christian character of the Catholic colleges in this study. At the same time this distinctiveness is qualified by the fact that 32 of these 42 differences were also true of the Protestant versus non-sectarian college deans.